Juridical Analysis of Divorce from Different Citizens Viewed from Indonesian Positive Law (Study Decision No 46/Pdt.G/2020/PN Tim) - Shidqi Mubarok, Muhammad; Dewi, Sartika; Abas, Muhamad (Dinasti Research, 2024)
Divorce is the dissolution of a marriage by a judge at the will of one of the two parties. The definition of divorce between different citizens can be interpreted as a separation between two individuals from different countries. This study aims to determine the authority of the Panel of Judges of the District Court of Timika City Papua in deciding divorce between different citizens, and to find out the considerations of the Panel of Judges of the Timika City District Court deciding in Number: 46/Pdt.G/2020/PN.Tim. The results of this study explain that the authority of the Panel of Judges of the Timkia City District Court to hear and decide cases of divorce of foreign nationals is seen based on the habitual residence or residence of the parties. The determination of the considerations of the Panel of Judges of the Timika City Court in deciding the case, refers to Law Number 1 of 1974 concerning Marriage, Article 207 of the Civil Code, the International Convention at The Hague in 1968, Article 831 of the Civil Procedure Law, and refers to judicial practices that have tried foreign divorces in Indonesia.